Is developing air cargo airports in the hinterland the way of the future?. (June 2017) - Yuen, Andrew; Zhang, Anming; Hui, Yer Van; Leung, Lawrence C.; Fung, Michael
Abstract: In this paper, we provide an analytical framework to capture the competition (and cooperation) between gateway and hinterland airports. We first investigate how airport charges at gateway and hinterland airports affect the equilibrium output in passenger and cargo markets. We further consider the Pearl River Delta region in China as a setting to conduct a numerical analysis. We find that the introduction of a hinterland airport is likely to lead to an improvement in the aggregate welfare of the gateway and the hinterland. If the connectivity between the gateway and hinterland airports is improved, then social welfare at the gateway and hinterland, benefits for shippers and passengers, and airport and airline profits at the gateway airport will increase. However, airport and airline profits at the hinterland airport will decrease. Highlights: Provide an analytical framework to capture the competition and cooperation between gateway and hinterland airports. Investigate how airport charges affect the equilibrium output in passenger and cargo. Consider the Pearl River Delta region in China as a setting to conduct a numerical analysis. The introduction of a hinterland airport is likely to lead to an improvement in the welfare.